Examining the implementation of multisectoral programs: The SELEVER process evaluation - Gelli, Aulo; Pedehombga, Abdoulaye; Awonon, Josue; Diatta, Ampa Dogui; Sanou, Armande; Becquey, Elodie; Diop, Loty; Eissler, Sarah; Heckert, Jessica; Ganaba, Rasmané (International Food Policy Research Institute, 2019)
The SELEVER study is a five-year impact evaluation in Burkina Faso designed to address key knowledge gaps on the impact of poultry value chain interventions on the diets, health and nutritional status of women and children.